What Section 15 has Achieved - Penney Kome (Atlantis)
Abstract The triumphant Canadian women’s constitution fight was a “political earthquake.” Massive lobbying efforts created or amended, inserted, and defended two sections relevant to sex equality—sections 15 and 28—in the Canadian Charter of Rights and Freedoms. Responses from both provincial and federal governments included the appointment in 1982 of the first woman justice of the Supreme Court, Bertha Wilson. A series of court challenges under section 15 resulted in a legal earthquake with respect to equal treatment for sexual preference. The presence of women justices on the Canadian Supreme Court—a political change—may produce the level of scrutiny that section 28 was intended to invoke.